(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Suicide is a silent epidemic which affects all the ages of population irrespective of gender. The major underlying causes are variable and multifaceted which differ in age groups. Failure in the examination, failure in love affairs, and failure to enjoy freedom are major ones in the child and young adult age groups. Divorce, demand for dowry, unwanted pregnancy, a failed marriage, domestic violence, inability to conceive, and conflicts resulting from extramarital affairs constitute the major cause of suicides in females. A demographic study was conducted in a tertiary care hospital and medical college situated in rural West Bengal to estimate the burden of suicide in the community catchment area of the jurisdiction. In one year of period, a total of 608 cases of suicidal deaths were reported of which the majority were male population and from the Hindu community. Hanging, poisoning, and burn injury were found to be the major causes of suicidal death and a few cases of drowning were also reported. Hanging was more prevalent than other causes of suicide. The highest frequency of suicidal death was found in the age group of 21 to 30 years of age followed by 31 to 40 years of age. This substantial loss of human life in the active years of working indicates the severity and gravity of the problem existing in society.